Hoe maak je het, lakmoes? Over de (semantische) productiviteit van Nederlandse ontleningen in het Pools / How are you, litmus? On the (semantical) productivity of the Dutch borrowings in the Polish language - Kowalska-Szubert, Agata (Werkwinkel, 2015)
Polish language contains hundreds of loan words from Dutch. They are rooted so firmly that they are capable of creating new words. This article presents the most common word-formation phenomena involving Dutch loan words. It also highlights their ability to form phrasemes and transfer meanings.